Sentiment Analysis on Tweets about Waste Problem in Yogyakarta using SVM - Nugroho, Robertus Adi; Wijono, Sri Hartati; Pinaryanto, Kartono; Gunawan, Ridowati; Sinungharjo, F.X. (International Journal of Applied Sciences and Smart Technologies, 2024)
Yogyakarta Province is facing a waste management problem. The closure of the only Integrated Waste Treatment Plant in Piyungan, Yogyakarta, has a huge impact in society life. Much waste generated from industries and homes cannot be handled appropriately until final disposal. This problem can be solved through government policies. Its effectiveness can be seen from the public response on social media. Sentiment analysis on social media, especially Twitter, can be efficiently conducted using Support Vector Machines. Data is directly obtained from Twitter, and text processing is performed on it. The accuracy rate of sentiment analysis using SVM on the topic of garbage in Yogyakarta is quite good at 87%.